Empowered love - Stosny, Steven (Ixia Press, 2018)
"Ever wonder why your self-control, rationality, and compassion seem to go out the window when dealing with your partner? Couples therapist and psychiatrist Steven Stosny explains it all in this revelatory book about the divide between our adult and our toddler brains. Too often, conflict in our intimate relationships reactivates our least-regulated "toddler" side, bringing out an instinctive desire to assert our own way and make everything a zero-sum game. Dr. Stosny shows the way toward overcoming these destructive impulses and nurturing our more loving and clear-eyed inclinations. Drawing upon his decades of experience in working with troubled marriages, he distills his insights into an actionable guide for embracing our best impulses in our relationships. Power Love is a valuable guide for married and live-in couples who struggle with an unhealthy dynamic; those already in individual or couples therapy who want a highly effective aid to help them communicate with their partner; and licensed therapists and counselors looking for an in-depth perspective on the developmental stages in play with relationship strife."--